Foreign policy in a transformed world - Webber, Mark (Prentice Hall, 2002)
This text examines foreign policy in relation to 'change and transformation.' It discusses traditional assumptions about foreign policy and foreign policy making, and develops a framework to facilitate analysis of the challenges faced by foreign policy makers in the late 1990s. The central elements of the framework are the foreign policy arena, decision-making and implementation. The book then applies the framework to a set of regional case studies, to explore the global and regional arenas and the challenges to which they give rise. Finally, specific case studies of two countries per region highlight the range of impacts for the changing global and regional context, to focus on the analysis of decision-making and implementation, and to illustrate the benefits of comparative analysis.